2007
DOI: 10.1108/14714170710721313
|View full text |Cite
|
Sign up to set email alerts
|

The development of an IFC‐based lifecycle costing prototype tool for building construction and maintenance

Abstract: Life-cycle costing (LCC) plays a very important role in the cost estimation and control of a building project. Although a number of LCC software tools have been developed in various CAD systems, the LCC applications based on interoperable data models, which can enhance comprehensive use of design information and historical data generated in various CAD systems, is still rare. The development presented in this paper focuses on interoperability issues in IT-based LCC applications and on improving LCC decision-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…Similarly, Fu et al developed a LCC tool based on an interoperable building information model [31]. It was shown that the developed tool could assist users in making appropriate decisions related to building design by evaluating various construction systems by assessing the LCC for all building components and by calculating a total LCC.…”
Section: -Backgroundmentioning
confidence: 99%
“…Similarly, Fu et al developed a LCC tool based on an interoperable building information model [31]. It was shown that the developed tool could assist users in making appropriate decisions related to building design by evaluating various construction systems by assessing the LCC for all building components and by calculating a total LCC.…”
Section: -Backgroundmentioning
confidence: 99%
“…Over time, this data could also be used to generate a historical database that in turn will be used for briefing, as well as predictive design. At present, the literature suggests a lack of longitudinal studies that focus on monitoring the performance and reliability of systems [71,72]. A major problem that limits the effectiveness of building decision support tools is the difficulty to obtain accurate data from various sources related to a building [73].…”
Section: Sources Of Wlc Datamentioning
confidence: 99%
“…An LCC practitioner in the case company characterizes the LCC calculations as "a complex and tedious task". Thus, as it is also stated in the literature, the AEC industry lacks useable software (Goh and Sun, 2016) and the calculation of LCC is, currently, a time-consuming procedure, prone to human error (Fu et al, 2007).…”
Section: Secondary Contradictionsmentioning
confidence: 99%